2006
DOI: 10.1111/j.1440-1746.2005.04090.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of chemical biliary duct embolization for chemical hepatectomy

Abstract: Chemical biliary duct embolization, especially using phenol plus cyanoacrylate, might achieve the effects of chemical hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Selection of an appropriate embolization agent that can complete embolization hepatic ducts of various sizes is the most important factor for successful chemical hepatectomy via CBDE. 5,12 Fu-Yu li, Jing-Qiu Cheng et al 12 suggested that phenol is not only the most efficient sclerosants of gall bladder mucosa, but is also a powerful antiseptic which might not only assist in ameliorating biliary infection which commonly accompanies hepatolithiasis, but also could commendably destroy the biliary mucosa and induced fibrous conglutination in the bile duct lumen, leading to partial occlusion of the large-size and middle-size biliary ducts, and complete occlusion of the small biliary ducts. 18,22,23 However, the biliary system could not be permanently occluded by using phenol or ethanol alone due to the regeneration of biliary mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Selection of an appropriate embolization agent that can complete embolization hepatic ducts of various sizes is the most important factor for successful chemical hepatectomy via CBDE. 5,12 Fu-Yu li, Jing-Qiu Cheng et al 12 suggested that phenol is not only the most efficient sclerosants of gall bladder mucosa, but is also a powerful antiseptic which might not only assist in ameliorating biliary infection which commonly accompanies hepatolithiasis, but also could commendably destroy the biliary mucosa and induced fibrous conglutination in the bile duct lumen, leading to partial occlusion of the large-size and middle-size biliary ducts, and complete occlusion of the small biliary ducts. 18,22,23 However, the biliary system could not be permanently occluded by using phenol or ethanol alone due to the regeneration of biliary mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, we explored the feasibility and efficacy of filling the diseased bile duct with chemical embolization agent to achieve chemical resection of the diseased bile duct and hepatic segment, and was able to establish the effects of chemical hepatectomy only in the periphery of the targeted hepatic lobe. [11][12][13][14][15] This study focuses on whether CBDE in the long-term manages to achieve complete fibrosis, "self-cut" and chemical hepatectomy in the whole embolized hepatic lobe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations